Features of the composition of the novels "Intibah"(The Awakening) and "Oʻtkan Kunlar" (Days Gone By). (Texas Journal of Philology, Culture and History, 2024)
In this article, the compositional features of Namik Kemal's “Intibah” (The Awakening) and Abdulla Qadiri's “O'tkan kunlar”(Days Gone By) novels, which are examples of the first novel genre of Turkish and Uzbek literature, are highlighted.